Trehalose-6-phosphate synthase as an intrinsic selection marker for plant transformation - Leymana, B.; Avonce, N.; Ramona, M.; Van Dijck, P.; Iturriaga, G.; Thevelein, J.M.
Insertion of foreign DNA into plant genomes occurs randomly and with low frequency. Hence, a selectable marker is generally required to identify transgenic plants. Until now, all selection systems have been based on the use of non-plant genes, derived from microorganisms and usually conferring antibiotic or herbicide resistance. The use of microorganism-derived genes however has raised biosafety concerns.We have developed a novel selection system based on enhancing the expression of a plant-intrinsic gene and the use of a harmless selection agent. Selection takes advantage of the reduced glucose sensitivity of seedlings with enhanced expression of AtTPS1, a gene encoding trehalose-6-P synthase. As a result, transformants can be identified as developing green seedlings amongst the background of small, pale non-transformed plantlets on high glucose medium. In addition, vegetative regeneration of tobacco leaf explants is very sensitive to high external glucose. Overexpression of AtTPS1 in tobacco allows selecting glucose insensitive transgenic shoots.
Keywords: PLANT TRANSFORMATION; INTRINSIC SELECTION MARKER; ATTPS1; TREHALOSE-6-PHOSPHATE SYNTHASE; GLUCOSE RESISTANCE; ARABIDOPSIS THALIANA; NICOTIANA TABACUM